Pathogenesis of bacterial infections in animals - Prescott, John F. (John Francis) 1949-; MacInnes, Janet I.; van Immerseel, Filip; Boyce, John; Rycroft, Andrew N. 1955-; Vazquez-Boland, Jose A. (Wiley-Blackwell, 2023)
"Pathogenesis of Bacterial Infections in Animals, Fifth Edition is a specialist reference that provides a comprehensive review of bacterial pathogens in animals and their interplay with complex disease processes, offering a complete understanding of how bacteria cause disease and covering recent advances in the field and new taxonomies. In the newly revised fifth edition, additional introductory chapters have been added to help to set the material in context, and more figures have also been added to improve understanding and comprehension throughout the text. A companion website presents the figures from the book in PowerPoint and references. This detailed reference includes novel approaches to controlling bacterial pathogens in light of growing concerns about antimicrobial resistance, with more than 70 expert authors sharing their wisdom on the topic. While molecular pathogenesis is a major aspect in almost every chapter, the authors have been careful to place pathogens in their broader context. Pathogenesis of Bacterial Infections in Animals, Fifth Edition is an essential resource for graduate students in veterinary medicine and animal science, microbiologists, virologists, and pathologists. It is the only book to cover this topic to this depth through the insight of dozens of qualified and practicing professionals"--